Exploring the clinical outcomes and molecular characteristics of Acinetobacter baumannii bloodstream infections: a study of sequence types, capsular types, and drug resistance in China - Jiao Chen; Yanting Shao; Zhibin Cheng; Guanghui Li; Fen Wan; Chenyan Gao; Danqin Wu; Dandan Wei; Dandan Wei; Yang Liu; Yang Liu; Rong Li (Frontiers in Cellular and Infection Microbiology)
BackgroundBloodstream infections (BSIs) caused by Acinetobacter baumannii have been associated with high mortality. To improve the outcomes of patients, this study explored the clinical characteristics and outcomes of patients with BSIs, as well as the phenotypic and genomic characteristics of these isolates.MethodsA retrospective cohort study was conducted involving A. baumannii BSIs cases from 2020 to 2023 in a tertiary hospital. The clinical characteristics of all A. baumannii isolates were evaluated. Virulence phenotypes of all isolates were evaluated using the growth curve, biofilm-forming assay, antiserum complement killing, and G.mellonella killing assay. Furthermore, whole-genome sequencing (WGS) was utilized to analyze genomic characteristics.ResultsThe 30-day mortality rate of 67 patients with BSIs was 55.22%. Patients in the death group had significantly lower platelet counts and higher CRP levels than those in the survival group. Additionally, higher rates of antibiotic use (≥2 classes) and greater carbapenem exposure were observed. Among the isolates, CRAb accounted for 80.6%, ST2 accounted for 76.12%, and KL2/3/7/77/160 accounted for 65.67%. The predominant KL type was KL3, found in 19.4% of the isolates. All ST2 and KL2/3/7/77/160 isolates were CRAb. Among the isolates, 90.7% of the CRAb isolates coharbored blaOXA-23 and blaOXA-66, while one coharbored blaNDM-1 and blaOXA-23. Compared with non-ST2 and non KL2/3/7/ 77/160 infections, ST2 and KL2/3/7/77/160 infections had higher mortality rates (66.0% vs. 23.5%, P=0.002; 65.90% vs. 34.78%, P=0.015). Patients with ST2 and KL2/3/7/77/160 infections underwent more invasive procedures, received two or more antibiotics and carbapenem therapy before isolation, and had lower serum albumin levels. These isolates exhibited significantly higher resistance to antimicrobial agents. No significant differences in virulence phenotypes were observed between the two groups, except for biofilm formation between the ST2 and non-ST2 groups (P=0.035). However, these isolates harbored more virulence genes related to iron uptake and biofilm formation.ConclusionThe mortality rate associated with BSIs caused by A. baumannii is high. It is of great significance for clinicians to pay attention to the risk factors of the clinical characteristics of patients and to identify the ST and KL types of the strains causing the infection at an early stage.